Peran Guru Bimbingan dan Konseling Dalam Pencegahan Kasus Bullying di MTsN Kota Palopo - Arfandi Arfandi; Arman Bin Anuar; Septya Suarja; Eva Windiani (Universitas Muhammadiyah Metro, 2025)
Bullying remains a serious challenge in educational settings and poses significant risks to students’ psychological well-being, academic engagement, and social development. This study aimed to explore the role of Guidance and Counseling (GC) teachers in preventing bullying at MTsN Kota Palopo. A qualitative approach with a case study design was employed to obtain an in-depth understanding of preventive practices implemented in the madrasah context. The participants included GC teachers as primary informants, as well as homeroom teachers, the school principal, and students as supporting informants. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that GC teachers play multiple roles in bullying prevention, functioning as trusted companions, mediators, and supervisors. Preventive efforts were implemented through individual counseling services, classroom guidance, information services, and the integration of Islamic values in counseling practices. Bullying prevention strategies also included Stop Bullying socialization during student orientation activities (Matsama), daily classroom monitoring, and close collaboration with parents and homeroom teachers. Furthermore, the study identified that bullying behavior is influenced by individual factors, family background, and the school environment. The results indicate that effective bullying prevention requires an integrative strategy that combines psychological approaches, religious values, and collaborative efforts among school stakeholders. This study highlights the strategic role of GC teachers in creating a safe, supportive, and bullying-free school environment and provides practical implications for strengthening preventive counseling services in madrasah settings.